Heritage Studies & Measured Drawings of Masjid Diraja Sultan Ala'eddin, Banting, Selangor - Mohd Ariffin, Noor Aziah; Asif, Nayeem; Abdul Rahim, Asiah; Azmin, Aida Kesuma; Sanusi, Aliyah Nur Zafirah; Razman, Badrul Amin; Jaafar Sidek, Amierul Syaddad; Muhammad Taufik, Muhammad Muzzammil; Min, Khant Oo; Rosli, Mohamad Azrul Azim; Roszaidi, Nur Aiman; Mohamad, Irfan Syamil; et al. (2021)
This work is one of the outcomes of AAR 3302 Heritage Studies, a core course that educates students to the understanding and practice of researching and documenting the heritage buildings in the Muslim world. The study on Masjid Diraja Sultan Ala'eddin, Banting Selangor was conducted in August 2020 and published in October 2020.